Swine unconventional T cells. (March 2022) - Wu, Miaomiao; Jiang, Qianling; Nazmi, Ali; Yin, Jie; Yang, Guan
Abstract: Pigs are important domestic livestock and a comprehensive understanding of their immune system is critical to improve swine vaccine efficacy. Pig models represent an excellent animal model for immunological studies because of their anatomical and physiological similarities to humans. A significant portion of pig immunological studies focused on characterizing the conventional T cell (Tconv) immune responses. These cells recognize peptides presented by major histocompatibility complex (MHC) proteins. In contrast, unconventional T cells are non-MHC-restricted and profoundly regulate conventional T cells. Key subsets of unconventional T cells reviewed here include natural killer T (NKT) cells, γδ T cells, mucosal-associated invariant T (MAIT) cells, intraepithelial lymphocytes (IELs), and two potential unconventional T cell subsets expressing NKp46 or CD11b. Unlike Tconvs, most of these cells recognize lipids, small molecule metabolites, or modified peptides, and they generally show simplified patterns of T cell receptor (TCR) expression and rapid effector responses. Here, we review that unconventional T cells are an abundant and critical component of the porcine immune system, summarize the current understanding of these cells, and highlight some of the key differences among mouse, human, and porcine unconventional T cells. Highlights: Unconventional T cells are key players in tissue homeostasis and immune responses. Different types of swine unconventional T cells. Features of porcine unconventional T cells are compared to that of other species.